2021
DOI: 10.3390/nu13051521
|View full text |Cite
|
Sign up to set email alerts
|

Diet Significantly Influences the Immunopathology and Severity of Kidney Injury in Male C57Bl/6J Mice in a Model Dependent Manner

Abstract: Diet is a leading causative risk factor for morbidity and mortality worldwide, yet it is rarely considered in the design of preclinical animal studies. Several of the nutritional inadequacies reported in Americans have been shown to be detrimental to kidney health; however, the mechanisms responsible are unclear and have been largely attributed to the development of diabetes or hypertension. Here, we set out to determine whether diet influences the susceptibility to kidney injury in male C57Bl/6 mice. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…Kidney damage in the three CKD models was further supported by significant regulation of gene expression markers of acute and chronic renal injury. In agreement with previous studies in ADI, UUO, and uIRI mice, we observed a marked upregulation of key markers of kidney injury, including Havcr1 [47,48,68], Lcn2 [68][69][70], and Spp1 [40,71]. These genes have been demonstrated to play an important role in renal regeneration and inflammatory responses in preclinical studies [72][73][74][75] and also implicated in human CKD pathogenesis [76,77].…”
Section: Discussionsupporting
confidence: 92%
“…Kidney damage in the three CKD models was further supported by significant regulation of gene expression markers of acute and chronic renal injury. In agreement with previous studies in ADI, UUO, and uIRI mice, we observed a marked upregulation of key markers of kidney injury, including Havcr1 [47,48,68], Lcn2 [68][69][70], and Spp1 [40,71]. These genes have been demonstrated to play an important role in renal regeneration and inflammatory responses in preclinical studies [72][73][74][75] and also implicated in human CKD pathogenesis [76,77].…”
Section: Discussionsupporting
confidence: 92%